Gender Inequality and Violence Against Women - Dilbar, Sadullayeva (Indonesian Journal of Social Development, 2024)
This article provides information on gender inequality, discrimination against women, violence against them, the consequences of early marriage of girls and the role of women in today's society, and provides examples of women working in high positions. The formation of a universal worldview in humans is a complex, non-hereditary process, and the inferiority of women compared to men causes many problems. It is very important for everyone to consider this point of view.